Morphological Differences Within Australopithecine Faces as a Reflection of Distinct Functional Adaptations - Kaszycka, Katarzyna A. (Anthropological Review, 1994)
It has been demonstrated in this paper that the australopithecine species differ in the morphology of their faces [Rak 1983], tooth sizes and proportions, and microscopic dental wear patterns, which are undoubtedly related to dietary habits [Grine, Kay 1988; Kay, Grine 1988]. Changes in diet created'stresses in the face because of the forces connected with chewing actions and powerful masticatory muscles, and the data seem to support the stress hypothesis. Moreover, allometric interpretations have failed to explain these different morphologies. Therefore, it seems reasonable to conclude that morphological differences within the australopithecine faces reflect distinct functional adaptations, i.e., dietary adaptations, and these differences are responses to stress caused by changes in diet.